Civic education as a variable and instrument for democratic regeneration - Canales Aliende, José Manuel (2018)
This article analyzes citizen education as a factor for the development and progress of our societies. Citizen education favors multiple behaviors, but in the first place it drives the good functioning of democracy. Citizens must know the true motives of the political game, its virtues and its defects, for the achievement of their objectives and for their defense. At present, the relationship between governments and education has been relegated to a secondary position, and this must change. The most relevant international organizations, such as the OECD and UNESCO, among others, emphasize the importance of education for the proper functioning of democratic structures, together with the development and progress of communities.